Hiperglicemia hospitalar: avaliação diagnóstica e terapêutica de pacientes não críticos internados nas enfermarias de clínica médica da FSCMPA - COSTA, Jeyson Kleyson Pinheiro da (2019)
Hospital hyperglycemia, defined as any glycaemia value above 140 mg / dl in the hospitalized patient, is still very little valued and inadequately treated in most hospitals in Brazil and in the world. The objective of this study was to identify how is done the diagnostic and therapeutic management of hyperglycemia in the noncritical patient, hospitalized in the medical clinic of the Fundação Santa Casa de Misericórdia do Pará. In this research, 104 patients were included, 65 male (62.5%) and 39 females (37.5%). Among the most common comorbidities as a reason for hospitalization, we can high light: chronic liver disease, congestive heart failure and renal failure. Despite the strong association between hyperglycemia in hospitalized patients and increased risk of complications and death, hyperglycemia remains inadequately treated. Studies such as this are essential for program planning to improve diabetes control and hyperglycemia in hospitalized patients.